Freeing the female body : inspirational icons - Mangan, J. A.; Fan, Hong, 1957- (Sport in the global society., 2001)
Stories of remarkable women who devoted their lives to the cause of women's physical liberation are told in this volume. They each shared the same ambition: to free women's bodies through sport. Scholars have studied the paradoxical importance of sport in both reinforcing the male-dominated status quo and emancipating women from traditional repression in both Western and Eastern worlds, but the role that individuals played in achieving the political and economic freedom of women through sport has been neglected. This collection records the bravery of these forgotten inspirational figures whose determination challenged and overcame convention, custom and prejudice to free women from the ranks of the sexualized, controlled and oppressed.